(3LhGgQ Gdabgs - (3GdWQGHdSj, CHh GdbGSe ` GHf GdHQGL, YHO GdYRjR Hf HMQ Hf YHO GdYRjR, J (B481 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B...(3aEfg deG cGfJ CjGOj MVQI GdbVGI GdCRjI GdLdGdjI GdefLRjI (B.. (3hCOGe bOQJgG hSYOgG YdjfG eeJOI (B...s
(3BNQgG (B:s
... (3aCdbjJ aj GdeGA MJi GQJaY eYG Edi MOg GdChd Ke bGd hRf gPg aajg hRf GdbjO hgPG ef CMSf GSJNQGLg (B.s
(3JHUQI GdYfhGf (B:s
(3LhGgQ Gdabgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\15s
(3GdPQjYI (B5 -183 (1225)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis